RANCANG BANGUN SISTEM INFORMASI BANK SAMPAH BERBASIS WEB MENGGUNAKAN METODE WATERFALL (STUDI KASUS: BANK SAMPAH DESA PAMEGARSARI) - Khairullah, Muhammad; Syamsu, Muhajir; Sestri, Elliya (Jurnal Sistem Informasi (JUSIN), 2024)
This research aims to design and develop a web-based waste bank information system using the waterfall method, focusing on the case study of the waste bank in Pamegarsari Village. The conventional waste management system in many villages relies heavily on manual processes, leading to inefficiencies in data recording, reporting, and management. The utilization of a web-based information system offers a potential solution to enhance waste management practices by enabling efficient data recording, processing, and reporting. The waterfall method is chosen for its sequential approach, which involves distinct phases including requirements gathering, system design, implementation, testing, and maintenance. By applying the waterfall method, this study seeks to provide a systematic and structured framework for developing the waste bank information system tailored to the specific needs and context of Pamegarsari Village. The findings of this research are expected to contribute to the improvement of waste management practices at the village level, promoting environmental sustainability and community engagement.